Exploring the Use of the Therapist’s Self in Therapy: A Systematic Review - Meera H. Alva; Sherin P. Antony; Kanak Kataria (Indian Journal of Psychological Medicine)
Purpose: This systematic qualitative review explored how psychotherapists use their self in therapy within the psychotherapy literature. It sought to examine the key documented ways through which the therapist’s self is intentionally used in therapy and the process of using the therapist’s self. Methods: Following PRISMA guidelines, databases including PubMed, ProQuest, APA PsycArticles, and APA PsycINFO were searched. The review question “How do therapists use their self in therapy?” guided the search using derivative keywords. Of the 149 screened articles, 20 underwent full-text review, and only four studies met inclusion criteria. Findings: All studies that met the inclusion criteria were from the West. Therapeutic self-disclosure (TSD) emerged as the primary way through which therapists used their self in therapy—notably, the only way documented in the studies reviewed. Studies discussed the nature, rationale, influencing factors, and effectiveness of TSD. This article elaborates upon the themes from the reviewed studies. It critically examines existing literature, lists avenues for future research, and discusses implications for psychotherapy practice. Conclusions: The review underscores a significant gap in empirical qualitative research regarding therapists’ use of their self beyond TSD in therapy. There is an urgent need for further exploration in this domain.